ANALYSIS OF THE EFFECT OF LOAD VARIATIONS ON THE THERMAL EFFICIENCY OF THE MUARA KARANG PLTG GAS TURBINE - Anugerah Banjarnahor; Hendri; Muhammad Ridwan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Gas turbines are one type of power plant with high flexibility, but their performance is greatly affected by variations in operating load. This study aims to analyse the effect of load variations on the thermal efficiency of Gas Turbine Unit 1.2 at the Muara Karang Gas Power Plant under three load conditions, namely 70 MW, 80 MW, and 90 MW. Actual operational data was used to calculate component work (compressor, combustion chamber, and turbine) and cycle thermal efficiency using thermodynamic calculation methods based on the Brayton Cycle. The calculation results were validated using Cycle Tempo and EES (Engineering Equation Solver) software with an average deviation of <5%. The results show that thermal efficiency increases as the operating load increases. At a load of 70 MW, the thermal efficiency was recorded at 30.30%, increasing to 30.76% at a load of 80 MW, and reaching a peak of 31.72% at a load of 90 MW. These findings prove that gas turbines operate most efficiently at loads close to their maximum capacity, so that operating at optimal loads can reduce specific fuel consumption and improve the energy efficiency of the plant.